State of the Art Bowel Management for Pediatric Colorectal Problems: Anorectal Malformations - Elizaveta Bokova; Wendy Jo Svetanoff; Joseph J. Lopez; Marc A. Levitt; Rebecca M. Rentea (MDPI AG, 2023)
Up to 79% of patients with anorectal malformations (ARMs) experience constipation and/or soiling after a primary posterior sagittal anoplasty (PSARP) and are referred to a bowel management program. We aim to report the recent updates in evaluating and managing these patients as part of the manuscript series on the current bowel management protocols for patients with colorectal diseases (ARMs, Hirschsprung disease, functional constipation, and spinal anomalies). The unique anatomic features of ARM patients, such as maldeveloped sphincter complex, impaired anal sensation, and associated spine and sacrum anomalies, indicate their bowel management plan. The evaluation includes an examination under anesthesia and a contrast study to exclude anatomic causes of poor bowel function. The potential for bowel control is discussed with the families based on the ARM index calculated from the quality of the spine and sacrum. The bowel management options include laxatives, rectal enemas, transanal irrigations, and antegrade continence enemas. In ARM patients, stool softeners should be avoided as they can worsen soiling.